Exposure to low-dose ionizing radiation and dementia mortality in Canadian nuclear power plant workers - Brianna Frangione; Laura A. Rodriguez Villamizar; Ian Colman; Franco Momoli; Estelle Davesne; Lydia Zablotska; Cheryl E. Peters; Paul Demers; Minh Do; Tim Prendergast; Philippe Prince; Paul J. Villeneuve (Environmental Research, 2026)

Assessing the role of the gut microbiome in methylmercury demethylation and elimination in humans and gnotobiotic mice - Genevieve L. Coe; Ian N. Krout; Mason Munro-Ehrlich; Catherine R. Beamish; Daria Vorojeikina; Daniel R. Colman; Eric J. Boyd; Seth T. Walk; Matthew D. Rand (Archives of Toxicology, 2023)

Daily changes in ambient air pollution concentrations and temperature and suicide mortality in Canada: Findings from a national time-stratified case-crossover study - Paul J. Villeneuve; David Huynh; Éric Lavigne; Ian Colman; Hymie Anisman; Cheryl Peters; Laura A. Rodríguez-Villamizar (Environmental Research, 2023)

Social integration of translocated wildlife: a case study of rehabilitated and released elephant calves in northern Kenya - Shifra Z. Goldenberg; Stephen M. Chege; Nelson Mwangi; Ian Craig; David Daballen; Iain Douglas-Hamilton; Nadine Lamberski; Moses Lenaipa; Reuben Lendira; Colman Lesowapir; Lekilia P. Lokooria; Mathew Mutinda; et al. (Mammalian Biology, 2022)
Conservation translocations have the potential to strengthen populations of threatened and endangered species, but facilitating integration of translocated individuals with resident populations remains a substantial challenge. Developing functional social relationships like cooperative partnerships or establishing clear dominance hierarchies may be critical to integration of released individuals. Developing such relationships has not received much attention in translocation research, especially for long-lived, socially complex animals for which establishment and navigation of social environments is often a lengthy process that requires sustained monitoring to understand. Here, we present a case study of the social associations of African savannah elephant ( Loxodonta africana ) calves that have been rehabilitated and released into a fenced wildlife sanctuary in northern Kenya with a resident population of elephants. We use focal follows of interactions pre-release and GPS tracking post-release to quantify social associations of calves with each other and with resident elephants at the release site. We demonstrate how this approach supports translocation monitoring by capturing temporal trends in social patterns within and between release cohorts and among released elephants and wild elephants already resident at the site during a transitional soft release period. Our results show that initial post-release social behavior of rehabilitated calves is related to histories of interaction with familiar individuals and cohort membership and that released calves increased their associations with residents over time. This information provides new behavioral insights for guiding elephant release projects, like the strength of relationships within and among release cohorts, the time to integration with the resident population, and the occurrence and increased incidence of societal fission–fusion. Further, this study provides an example of the utility of animal behavior research to achieve and assess progress towards conservation objectives, and to develop monitoring tools for conservation managers.

Observed and projected intra‐seasonal variability of Australian monsoon rainfall - Aurel Moise; Ian Smith; Josephine R. Brown; Robert Colman; Sugata Narsey (International Journal of Climatology, 2020)
Indices derived from daily rainfall time series are used to measure “burst” features of the northern Australia monsoon, corresponding to one or more days of heavy rainfall. These indices include number of burst days, numbers and durations of burst events, and average intensity. The results using observational data show how these features can vary from one year to the next, and how they can vary from the station scale (Darwin) to the regional scale (northern Australia). The results from Coupled Model Intercomparison Project Phase 5 (CMIP5) climate model simulations under both historical and future greenhouse gas conditions have also been analysed and indicate how well models can capture these features and how they might change by the end of the 21st century under a high emissions scenario. While most models provide a reasonable simulation of present‐day burst features, there is little consensus for a significant change to seasonal rainfall totals when looking at the full CMIP5 ensemble. A subset of models with detectable skills with respect to the Madden‐Julian Oscillation shows evidence for an increase in the seasonal total rainfall amount and most other monsoon metrics, except a slight decrease in the number of burst events. This is consistent with a basic thermodynamic response to warming and consistent with findings elsewhere. However, the Australian monsoon is strongly influenced by the large‐scale circulation and there remains some doubt about whether we can confidently diagnose all the changes to monsoon bursts that could occur given the limited ability of many of the current generation of models to simulate tropical cyclones, the Madden‐Julian Oscillation and other relevant features.

Informing CITES Parties: Strengthening science‐based decision‐making when listing marine species - Kim Friedman; Matias Braccini; Matthew Bjerregaard‐Walsh; Ramón Bonfil; Corey J. A. Bradshaw; Stephen Brouwer; Ian Campbell; Rui Coelho; Enric Cortés; Wetjens Dimmlich; Michael G. Frisk; Irene Kingma; et al. (Fish and Fisheries, 2020)
International trade in vulnerable marine species is regulated once they are listed in CITES Appendices (the Convention on International Trade in Endangered Species of Wild Fauna and Flora). Parties to the Convention submit proposal(s) 150 days prior to the CITES Conference for voting on the inclusion of new species in Appendices I and II, making a case for why CITES listing criteria are met in each case. Before the vote, Parties receive advice from (a) the Food and Agriculture Organization of the United Nations, (b) the International Union for Conservation of Nature—TRAFFIC and (c) the CITES Secretariat, among others. This paper offers an expert review of listing processes, which are the subject of much debate in fishery and environment‐protection communities, looking at two specific cases: silky shark ( Carcharhinus falciformis, Carcharhinidae) and bigeye thresher shark ( Alopias superciliosus, Alopiidae). The reviewers determine that the evidence made available to voting Parties is substantial, but suffers from non‐standard presentation across assessments. The best available data are not always presented or described transparently in relation to CITES criteria. An extension of the assessment period, as well as the opportunity to refute evidence, has been suggested as ways to support more informed and effective decision‐making by CITES Parties, whose composition of delegations varies greatly in their experience of marine species management and trade. Experts welcomed a greater coherence of advice between fishery and non‐fishery sources in the long term, and proposed a range of suggested improvements for the delivery of information and advice to CITES Parties.